One Country, Two Systems? he Future of Hong Kong from 2047 (Comillas Journal of International Relations, 2021)
This article analyses from a Constitutional Law point of view, the factors that characterize Sino- Hongkonese relations with the aim of analysing the future of the One Country, Two Systems regime. The strong protests that took place in 2019 and the latest actions taken by the Beijing government, such as the approval of the national security law, constitute a clear sign of the tension experienced in the region in view of the uncertain future of the Hong Kong regime, which appears to be limited by Article 5 of its Basic Law to the 30th of June of 2047. In view of this uncertainty, this research assesses three possible future scenarios: Hong Kong becomes part of Mainland China, a democratic transition takes place in the region, or the One Country, Two Systems regime endures over time.
Keywords: Hong Kong; China; One Country Two Systems; Chinese dream; localism